2013
DOI: 10.1167/iovs.13-12093
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between 24-Hour Mean Ocular Perfusion Pressure Fluctuation and Rate of Paracentral Visual Field Progression in Normal-Tension Glaucoma

Abstract: Medically treated NTG eyes with greater 24-hour MOPP fluctuations (HMF) had faster PVF defect progression than eyes with stable 24-hour MOPP (LMF). Twenty-four hour MOPP fluctuation associated significantly with PVF progression velocity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 36 publications
2
52
0
Order By: Relevance
“…76 We found that ganglion cell complex thickness in the papillomacular bundle was significantly associated with central visual function, as measured by best-corrected visual acuity and the central 4 measurement points of the Humphrey field analyzer. 77 We also found that blood flow on the temporal side of the ONH was highly associated with ganglion cell complex thickness.…”
Section: Macular Function and Obf In Glaucomamentioning
confidence: 68%
“…76 We found that ganglion cell complex thickness in the papillomacular bundle was significantly associated with central visual function, as measured by best-corrected visual acuity and the central 4 measurement points of the Humphrey field analyzer. 77 We also found that blood flow on the temporal side of the ONH was highly associated with ganglion cell complex thickness.…”
Section: Macular Function and Obf In Glaucomamentioning
confidence: 68%
“…38 In brief, the OAG patients were classified into two groups based on PD probability maps of SITA 24-2 VF testing. The CVFD group included patients with clusters of three significant points, with a probability of less than 5%, or two or more test points with a probability of less than 1% or smaller, on a PD probability map within the superior or inferior hemifield of the central 108 regardless of the presence of VF defects outside the central 108 (Fig.…”
Section: Classification Into Cvfd and Pvfd Groupsmentioning
confidence: 99%
“…One factor influencing this process is the ocular perfusion pressure (OPP) [1317]. OPP is the difference between systemic blood pressure and the RVP.…”
Section: Introductionmentioning
confidence: 99%